Associations between heavy metal exposure and vascular age: a large cross-sectional study - Yuntao Feng; Chengxing Liu; Litang Huang; Jun Qian; Na Li; Hongwei Tan; Xuebo Liu (Journal of Translational Medicine)
Abstract Background Heavy metal exposure is an emerging environmental risk factor linked to cardiovascular disease (CVD) through its effects on vascular ageing. However, the relationship between heavy metal exposure and vascular age have not been fully elucidated. Methods This cross-sectional study analyzed data from 3,772 participants in the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2016. We measured urinary concentrations of nine heavy metals and assessed their associations with vascular age, estimated pulse wave velocity (ePWV) and heart vascular age (HVA). Additionally, sex-stratified analyses, Weighted Quantile Sum (WQS) regression and Bayesian Kernel Machine Regression were conducted to explore the effects of individual and mixed metal exposures. Results Exposure to metals such as cadmium (Cd) cesium (Cs), cobalt (Co), and lead (Pb) was significantly associated with increased vascular age, with odds ratios (OR) ranging from 1.05 to 3.48 in full adjusted models. Sex-stratified analyses indicated that individual metal including cobalt (Co) and cadmium (Cd) exposures had a more substantial impact on males. WQS analysis consistently showed combined heavy metals exposure had stronger associations with increased vascular age in men (OR for HVA = 3.89, 95% CI 2.91–5.28). Conclusions This study highlights a significant association between heavy metal exposure and increased vascular age. Stratified analyses illustrated men might be more susceptible to the combined effects of multiple heavy metal exposure. The findings underscore the importance of considering sex-specific responses and interventions measures in cardiovascular risk assessments and managements. Further research is needed to validate these findings and to develop more precise public health strategies targeting environmental risks. Graphical Abstract